PENERAPAN MODEL GROUP INVESTIGATION BERBASIS MEDIA HERBARIUM MENGGUNAKAN APLIKASI PICTURETHIS-PLANT IDENTIFIER UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA - Perayanti Sinaga, Dian; Rajagukguk, Salome; Rolita, Ria (Jurnal Metabio, 2024)
This study aims to determine the effect of implementing the group investigation model based on herbarium media using the PictureThis-Plant Identifier application on students' creativity and learning outcomes. This research is a field research with a quantitative approach using the Pretest-Posttest Control Group Design research design. The results showed that the implementation of the group investigation model based on herbarium media using the PictureThis-Plant Identifier application had a significant effect on increasing students' learning creativity. This is indicated by the value of tcount > ttable (45.443 > 1.681) at a significance level of 0.05. The experimental class using this learning model had a higher average score of learning creativity compared to the control class. The implementation of the group investigation model based on herbarium media using the PictureThisPlant Identifier application also had a significant effect on improving student learning outcomes. The data analysis showed that the value of tcount > ttable (92.217 > 1.681) at a significance level of 0.05. The average posttest score of the experimental class (82.50) was higher than the control class (77.50).